Efeito da adição de Ni na microestrutura bainítica de um novo aço para roscas e cilindros de plastificação de polímeros - Bacalhau, José Britti (2019)
Nitriding steels, such as DIN 1.8550, are used in the manufacture of screws and barrels for injection molding machines and plastic extruders. The hardening process of DIN 1.8550 occurs via water or oil quenching followed by tempering, and, it is common to experience distortions in bars subjected to severe temperature gradients. Residual stresses arising from cold straightening of steel bars and/or remaining from heat treatment cause, during the machining of components, problems related with geometric variations on screws and/or deviations in deep drilling of barrels. The objective of this work was the technological development of a new steel for screws and barrels, which has high dimensional stability since it allows hardening via still air cooling. It was produced four chemical compositions of low-carbon steels with variation only in the Ni content. Through dilatometry tests, it was verified that Ni delayed the transformation kinetics of ferrite and pearlite, and, favored the formation of bainite and martensite. In the studied bainitic steels, Ni also promoted the formation of lower bainite at the expense of upper bainite. The steel with 1.40% Ni presented a refined microstructure mainly composed of lower bainite, with homogeneous precipitation of alloy carbides in the bainitic ferrite lath. Steels with low Ni contents, 0.03% and 0.70%, exhibited a microstructure mainly composed of upper bainite, with alloy carbides precipitation in the boundaries of the bainitic ferrite packages. The 1.40% Ni steel showed the best combination of results regarding toughness, microstructure and hardenability, and, for that reason it was also produced in industrial scale. The steel hardening process, with in-line quenching via still air cooling, was industrially validated achieving the production of a very homogeneous bainitic steel. The work was completed with the full-scale manufacture of a screw and a barrel from extruder machines, therefore the technological development covered from laboratory phase to field tests.